Development and validation an instrument for evaluating epistemic knowledge: Educational biology context - Raudlah Melinda Sidik; Ana Ratna Wulan; K. Kusnadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The research developed and validated EKSAI (Epistemic Knowledge Science Assessment Instrument), an assessment tool for epistemic knowledge in science education. The background is that 21st-century challenges demand a transformation in science education, with a focus on understanding how scientific knowledge is developed and evaluated, which is essential for students' science literacy. In the context of global scientific progress and rapidly advancing technology, students need more than just factual knowledge; they must understand the nature and justification of scientific claims. However, this epistemic dimension is often overlooked in classroom assessments. Indonesia's low PISA rankings highlight the urgency of developing a valid assessment tool. The aim of this study was to develop a tool that evaluates learning experiences and epistemic assessment practices. An R&D method was used, involving expert validators and 102 high school students, with Rasch Model analysis and Cronbach's alpha for validity and reliability. The results show that this tool has very high reliability (Cronbach's Alpha 0.91) even though one item was removed because it did not meet the Rasch criteria. In conclusion, EKSAI is a powerful tool, ready to evaluate teachers' assessment practices and support the improvement of science literacy in Indonesia.